Contrast-enhanced ultrasound of the pediatric brain - Hwang, Misun; Barnewolt, Carol E.; Jüngert, Jörg M.; Prada, Francesco; Sridharan, Anush; Didier, Ryne A. (Pediatric Radiology, 2021)
Brain contrast-enhanced ultrasound (CEUS) is an emerging application that can complement gray-scale US and yield additional insights into cerebral flow dynamics. CEUS uses intravenous injection of ultrasound contrast agents (UCAs) to highlight tissue perfusion and thus more clearly delineate cerebral pathologies including stroke, hypoxic–ischemic injury and focal lesions such as tumors and vascular malformations. It can be applied not only in infants with open fontanelles but also in older children and adults via a transtemporal window or surgically created acoustic window. Advancements in CEUS technology and post-processing methods for quantitative analysis of UCA kinetics further elucidate cerebral microcirculation. In this review article we discuss the CEUS examination protocol for brain imaging in children, current clinical applications and future directions for research and clinical uses of brain CEUS.
CRIS-Team Scopus Importer:2021-03-05
Keywords: Brain; Children; Contrast-enhanced ultrasound; Epilepsy; Hypoxic–ischemic injury; Neurovascular disease; Stroke; Tumor; Ultrasound; Ultrasound contrast agents